Overfeeding and obesity in young children with positive pressure ventilation via tracheostomy following cardiac surgery. (3rd October 2020) - Tsuda, Takeshi; Hehir, David A.; Thacker, Deepika; Lamma, Allison; Tearl, Donna; Gidding, Samuel S.
Abstract: Objectives: Infants with CHD requiring positive pressure ventilation via tracheostomy are especially vulnerable to malnutrition following cardiac surgery. Current post-operative feeding recommendations may overestimate the caloric needs. Design: We retrospectively studied infants requiring tracheostomy after cardiac surgery. Anthropometric and nutritional data were collected, including caloric goals, weight-for-age z score, length-for-age z score, and weight-for-length z score. Changes in anthropometrics over time were compared to ascertain the impact of nutritional interventions. Data were shown as mean ± standard deviation. Results: Nineteen infants with CHD required tracheostomy at 160 ± 109 days (7–364 days), 13 had reparative surgery, and 6 had palliative surgery for single ventricle. The indications for tracheostomy consisted of airway abnormality/obstruction (n = 13), chronic respiratory failure (n = 7), and/or vocal cord paresis (n = 2). Initial maintenance nutritional target was set at 100–130 cal/kg per day. Fourteen patients (73.7%) became obese (maximum weight-for-length z score: 2.59 ± 0.47) under tracheostomy and gastrostomy feeding, whereas five patients did not (weight-for-length z score: 0.2 ± 0.83). Eight obese patients (weight-for-length z score: 2.44 ± 0.85) showed effective reduction of obesity within 6 months (weight-for-length z score: 0.10 ± 0.20; p < 0.05 compared with pre-adjustment) after appropriate feeding adjustment (40–90 cal/kg per day). Overall mortality was high (31.6%) in this population. Conclusion: Standard nutritional management resulted in overfeeding and obesity in young children with CHD requiring positive pressure ventilation via tracheostomy. Optimal nutritional management in this high-risk population requires close individualised management by multidisciplinary teams.